Observing The Parameter Dependant System On The Formation Of Lag Phase Curve In A Bacteria Growth - Chang, Chee Wing (Universiti Sains Malaysia, 2021)
Predictive biology plays an important in forecasting the behaviour of the microorganismunder the unpredictable environment condition such as temperature and pH. In order to precisely simulate the growth of the microorganism, several growth models had been proposed. Logistic model, modified Gompertz equation, Luedeking-Piret model and Monod model are the models that were studied in this work. These models composed of several growth parameters which have significant impact on the growth curve. Typically, growth curves are presented in the form of sigmoidal curve. Growth parameters such as maximum specific growth rate (µmax) and lag time (